Brief cognitive therapy for avoidant personality disorder - Rees, Clare; Pritchard, R. (American Psychological Association Inc., 2015)
Avoidant personality disorder (APD) is associated with a high level of impairment in multiple areas of functioning. However, research on the treatment of APD is scarce, and there is an absence of empirically evaluated effective treatment approaches available. This study offers a preliminary investigation of the use of brief cognitive therapy to treat APD. Two individuals, both with a principal diagnosis of APD, but who also possessed a number of comorbidities, participated in 12 weekly sessions. A series of diagnostic symptom severity, global functioning, and self-report measures were completed at pretreatment, posttreatment and at 6-week follow-up. In addition, regular monitoring of each participant's strength of belief in 4 personally identified cognitions associated with APD was completed. Reductions in APD symptoms, associated negative affect, and increases to quality of life were observed for both participants at posttreatment and follow-up phases. Results suggest that brief cognitive therapy may be an effective treatment for APD and that further studies with larger samples are warranted.